The Ethical Foundations of Early Daoism - Lee, Jung H. author. aut Link
XI, 186 p.
Keywords: The Ethical Foundations of Early Daoism: Zhuangzi's Unique Moral Vision argues that we can read early Daoist texts as works of moral philosophy that speak to perennial concerns about the well-lived life in the context of the Way. Lee argues that we can interpret early Daoism as an ethics of attunement.